Factors Influencing Participation of Rural Women Farmers in Agricultural Activities in Ranau, Sabah, Malaysia: An Exploratory Factor Analysis - Norsida Man; Umar Abdulmumini; Shin Yee Siaw (Universitas Sebelas Maret, 2024)
Globally, rural women farmers benefited from only 5% of agricultural extension information, and also only 10% of the agricultural extension facilities, this affects their engagement in agricultural development resulting in an increased rate of poverty and lack of the necessary knowledge of agricultural practice. This study aimed to determine the internal and external factors influencing rural women farmers’ participation in agricultural activities in rural areas of Malaysia. The study was conducted in Ranau, Sabah, Malaysia. A sample size of 248 rural women farmers was selected using simple random sampling. A five-point Likert scale questionnaire was used for data collection. Collected data were subjected to descriptive and factor analysis using Statistical Packages for Social Science (SPSS) version 26. The findings indicated that the factors affecting rural women’s participation in agricultural activities in Ranau, Sabah, encompassed access to financial and agricultural inputs, social culture, land rights, access to land, technology adoption, participation in farm management decisions, limited scope of agricultural policy and access to resource and support for women in agriculture. The present study has provided insights into the factors contributing to women’s participation in agriculture activities. The study suggests that a theoretical model should be proposed to test the relationship between these factors and women’s participation in agriculture, along with research to identify solutions for reducing identified barriers.